Millimetre wave antenna for tracking applications in 60GHz band - Ur Rahman, Md. Fahim; Islam, Md. Sumon; Khan, Walid Uddin; Yeashmin, Purnima (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2018.